ESTIMASI WAKTU REPARASI KM. WILIS MENGGUNAKAN CRITICAL PATH METHODE - Idsan, Muhammad Akhsal; Rachman, Taufiqur (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Accurate time estimation is the key to the success of KM Wilis repair activities at PT Industri Kapal Indonesia (Persero). Delays in ship repair activities will be able to cause losses for shipowners in fulfilling shipping transport service schedules. This study aims to develop a reparation plan for KM. Wilis with critical path method in order to obtain the optimal duration of repair work. Based on the KM Wilis repair list, repair activities were identified into smaller components (work breakdown structure) to determine the relationship between preceding and preceded activities. The repair list is also used as a guideline for data analysis, which includes job descriptions, labour, duration, and work volume. Critical Path Method as a time management method is used to identify activities that are on the critical path. KM Wilis repair time estimation obtained a duration of 33 days with critical path activities including tug boat services, docking services, hull cleaning work with water jets, hull cleaning work with scrap, unloading skerm bush pintles and rudder leaf pens, dismantling of the lowered rudder leaf on the dock floor, making new left rudder leaves, reinstalling rudder leaves, undocking services, tug boat services and sea trials.